PENGARUH INDEPENDENSI, PENGALAMAN KERJA, DUE PROFESSIONAL CARE DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT - Wiratama, William Jefferson; Budiartha, Ketut (E-Jurnal Akuntansi; Vol 10 No 1 (2015), 2015)
This study aims to analyze and obtain empirical evidence about the effect of independence, work experience, due professional care, and accountability of auditors on audit quality auditors owned Public Accounting Firm in Denpasar. This research was conducted using a survey method with a questionnaire. The population was auditors who listed in the Directory IAPI in Denpasar. This study uses primary data obtained by distributing questionnaires to 52 respondents. Data analysis was performed with multiple linear regression method. This study found that independence, work experience, professional due care and accountability of auditors have a significant positive effect on audit quality.
Keywords: Independence, Experience, Due Professional Care, Accountability, Audit Quality